Needs of the «digital» generation: reverse learning technology - Zhusup kyzy N. (Scientific Dialogue: Issues of Humanitarian Studies)
the article examines current approaches and methods of reverse learning in the digitalization of education as an inevitable process for the system of higher professional education. Reverse learning assumes that, using the capabilities of information and communication technologies in the educational process, it is possible to combine traditional and distance learning without reducing academic hours. Thus, by transferring some of the material into the digital environment, during classroom lessons more attention is paid to the formation and development of practical skills in all types of activities in a foreign language.
Keywords: иностранный язык; информационное общество; информационно-коммуникационные технологии; foreign language; information and communication technologies; information society; цифровизация образования; Digitalization of education; reverse learning; traditional and distance learning; обратное обучение; традиционное и дистанционное обучение